Gender and Protest On the Historical and Contemporary Interrelation of Two Social Phenomena - Mohammed, Jowan A.; Jacob, Frank (De Gruyter, 2023)
For centuries women had to protest to gain equality. Their demands were often matched by counter-protest from conservative forces within historical societies.The present volume will take a closer look at the interrelationship between gender and protest and also analyze and discuss the diverse impacts of this special coherence of the two historical forces.